Evaluation of calretinin immunohistochemistry as an additional tool in confirming the diagnosis of Hirschsprung disease - Małdyk, Jadwiga; Rybczyńska, Jolanta; Piotrowski, Dariusz; Kozielski, Rafał (Polish Journal of Pathology, 2014)
Hirschsprung disease (HD) is a congenital malformation defined as the absence of myenteric and submucosal ganglion cells (GCs) in the distal rectum and variable length of the contiguous bowel. The aim of this study was to assess the utility of calretinin immunochemistry in comparison with that of standard histology complemented with acetylcholinesterase (AChE) histochemistry routinely employed at our institution to evaluate rectal biopsies carried out for suspicion of HD. Twenty-one rectal biopsies were reviewed, including 14 from patients with suspected HD, 6 from infants with necrotizing enterocolitis (NEC), and 1 from a patient diagnosed with spontaneous intestinal perforation (SIP). Sections stained with hematoxylin-eosin (HE) revealed absence of ganglion cells in 13 cases which included 11 patients with HD and 2 patients with NEC. Among 13 cases of aganglionosis the AChE reaction pattern was consistent with HD in 2 patients. Calretinin positivity was observed in all rectal biopsies showing the presence of GC, and the staining was consistently absent in all cases of aganglionosis. In 6 rectal biopsies in which abnormal acetylcholinesterase (AChE) staining was not seen, loss of calretinin immunoreactivity helped establish the diagnosis of HD.